An automatic collision avoidance algorithm for multiple marine surface vehicles - Hedjar, Ramdane; Bounkhel, Messaoud (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, unmanned surface vehicles have been widely used in various applications from military to civil domains. Seaports are crowded and ship accidents have increased. Thus, collision accidents occur frequently mainly due to human errors even though international regulations for preventing collisions at seas (COLREGs) have been established. In this paper, we propose a real-time obstacle avoidance algorithm for multiple autonomous surface vehicles based on constrained convex optimization.
Keywords: unmanned surface vehicles; obstacle avoidance; control allocation; constrained convex optimization